Factors Influencing the Consumption of Factor X (Stuart-Prower Factor) during Intrinsic Coagulation - Niemetz, J (Thrombosis and Haemostasis, 1967)
1. Factor X is consumed during in vitro intrinsic coagulation of normal blood when both surface activation and either bovine AHG or phospholipid such as cephalin, hemolysate, PS, PE, or mixture of PS and PE are present. Neither surface activation, AHG or phospholipid alone produces significant consumption of factor X.2. Consumption of factor X did not occur in hemophilic bloods (AHG or PTC deficient) when both surface activation and phospholipid were present.3. The consumption of factor X in blood from human subjects, with high factor VIII levels, when surface activation was provided, was only moderately augmented compared with results in blood with a normal factor VIII level.4. The consumption of factor X in the blood of a patient with a SLE inhibitor was similar to that in normal blood when both contact activation and phospholipids were supplied.